Kadar Nutrien, Mineral dan Anti Nutrien Biji Berbagai Aksesi Arbila (Phaseolus lunatus L.) Berkategori Berat dari Kabupaten Kupang sebagai Pakan - Bernadete Barek Koten; Jacobus S. Oematan; Resa L. Talan; Andreas Trilalan Moruk; Redempta Wea; Noldin Abolla; Allan Prima Titong (Pastura: Jurnal Ilmu Tumbuhan Pakan Ternak, 2024)
The study aimed to evaluate the nutrient, mineral, and antinutrient levels of seeds of various accessions ofarbila (Phaseolus lunatus L.) in the heavy category from Kupang Regency as feed. This study was conducted in Kupang Regency and the Politani Animal Nutrition and Feed Laboratory for 8 months (April - November 2023). The materials and tools were seeds from 16 arbila accessions and digital scales. The working procedures were seed collection, identification and grouping of seeds in accessions based on seed morphology, sample preparation, and analyzing nutrient, mineral and anti-nutrient levels of arbila seeds in the weight category. The variables measured were dry matter content (DM - %), crude protein content (CP - % DM), crude fiber content (CF - % DM), ether exctract (EE - % DM), and ash (%), mineral content in the form of calcium (Ca), phosphorus (P) and potassium (K), and anti-nutrients in the form of cyanide acid (ppm) and phytic acid (%) of the arbila seeds. The data were then described. The results showed that there were 16 arbila accessions with seeds in the categories of weight, nutrient content, minerals, and anti-nutrients of arbila seeds from various accessions varied and were different for each accession. The nutrient content was 86.63 - 88.48% DM content, 15.75 - 26.88% CP, 1.30 - 2.02% EE, 5.73 - 8.77% CF, 58.87 - 71.20% NFE content, and 3.73 - 5.97% ash content. The mineral content is 0.30-0.57% Ca, 0.41-0.79% P, 1.10-1.41% K. The anti-nutrient content is 125.09 – 318.51 ppm cyanide acid and 0.04-0.52% phytic acid. It was concluded that the nutritional, mineral, and anti-nutrient values of arbila seeds in the heavy category varied and were determined by the arbila accession. ABSTRAK Penelitian bertujuan untuk mengevaluasi kadar nutrien, mineral, dan anti nutrien biji berbagai aksesi arbila (Phaseolus lunatus L.) berkategori berat dari Kabupaten Kupang sebagai pakan. Penelitian ini telah dilaksanakan di Kabupaten Kupang dan Laboratorium Nutrisi dan Pakan Ternak Politani selama 8 bulan (April - November 2023). Bahan dan alat yang digunakan adalah biji dari 16 aksesi arbila, dan timbangan digital. Prosedur kerjanya adalah pengumpulan biji, pengidentifikasian dan pengelompokan biji dalam aksesi berdasarkan morfologi biji, preparasi sampel, dan  menganalisis kadar nutrien, mineral dan anti nutrien dari biji arbila berkategori berat. Variabel yang diukur adalah kadar bahan kering (BK - %), kadar protein kasar (PK - % BK), kadar serat kasar (SK - % BK), kadar lemak kasar (LK - % BK), dan abu (%), kadar mineral berupa kalsium (Ca), phosphor (P) dan kalium (K), serta anti nutrien berupa asam sianida (ppm) dan asam fitat (%) dari biji arbila tersebut. Data kemudian dideskriptifkan. Hasil penelitian menunjukkan bahwa terdapat 16 aksesi arbila dengan biji berkategori berat kadar nutrien, mineral dan anti nutrien biji arbila dari berbagai aksesi bervariasi dan berbeda untuk setiap aksesinya. Kandungan nutriennya yaitu 86,63 – 88,48%kadar BK, 15,75 – 26,88% PK, 1,30 – 2,02% LK, 5,73 – 8,77% SK, 58,87 – 71,20% kadar BETN dan 3,73 – 5,97% kadar abu. Kadar mineralnya adalah 0,30-0,57% Ca, 0,41-0,79% P, 1,10-1,41% K. Kadar anti nutriennya adalah 125,09 – 318,51 ppm asam sianida dan 0,04-0,52% asam fitat. Disimpulkan bahwa nilai nutrien, mineral dan anti nutrien dari biji arbila berkategori berat adalah beragam dan ditentukan oleh aksesi arbila.